Hypertensive emergency presenting with an isolated celiac artery dissection: A rare case study. (2016) - Swergold, Natalie; Kozusko, Steven; Rivera, Carlos; Sturt, Cindy
Highlights: To the best of our knowledge, we present the 25th case of isolated celiac artery dissection. This is the first case of hypertensive emergency induced spontaneous isolated celiac trunk dissection in literature. Visceral artery dissection is a rare commodity, and celiac artery dissection is less common than dissection in the SMA. It is a difficult diagnosis to make on history and physical alone, necessitating contrast enhanced CT imaging. Our patient was managed nonoperatively with a labetalol drip and did well. Abstract: Introduction: To our knowledge the most recent article on celiac dissection was published in 2015 and reported 24 known cases of spontaneous isolated celiac trunk dissection [2]. While some of those cases reported hypertension as a risk factor, no other case presents as hypertensive emergency with an isolated celiac artery dissection. Presentation of case: A 43 year-old man with a past medical history of uncontrolled hypertension, for which he had reportedly been non-compliant with follow-up, presented with complaints of severe, sudden-onset epigastric pain which was non-radiating and constant for 1 hour prior to arrival. On CT an intimal flap was noted within the celiac trunk, starting at the origin and extending into the left gastric, splenic, and the common hepatic arteries. Discussion: The most common symptom in patients with celiac artery dissection is acute or chronic epigastric or abdominal pain [2, 4, 9, 11]. The crux of the diagnosis of this condition relies on contrast enhanced CT. The superiority of the CT scan is because of the contrast tracking capability [11]. The two most common risk factors for celiac artery dissection are hypertension followed by vasculitis. Patients can be managed nonoperatively or with one of a few operative procedures. Conservative treatment consists of anticoagulants, antihypertensives, and antiplatelet therapy [2]. Conclusion: To the best of our knowledge, we present the 25th case of isolated celiac artery dissection. This is the first case of hypertensive emergency induced spontaneous isolated celiac trunk dissection in literature. Our patient was managed primarily with a labetalol drip.